Eating approach of bereaved individuals: A protocol proposal - Fialho de Sousa CAMPOS, Maria Teresa; do Carmo Gouveia PELUZIO, Maria; Amaral ARAÚJO, Raquel Maria (Revista de Nutrição, 2023)
Objective The objective of this manuscript was to discuss the care inherent to the methodological procedures for food research in bereavement situations, proposing the use of a conduct protocol. Methods The protocol for food research in bereavement is presented, based on the critical review of literature and the experience with food surveys applied to bereaved people. Results The conduct protocol is divided into three moments corresponding to the meetings and the steps of approach are discussed in these care services. This research seeks to problematize this investigation, outlining the phases of coping with bereavement that involve greater adherence, from these individuals, to food surveys. Conclusion The conduct protocol guiding the investigation of eating habits of bereaved individuals provides information that allows the professional to evaluate the infl uence of bereavement on food in addition to allowing a greater adherence of these individuals to the survey.